2007
DOI: 10.1111/j.1750-3841.2007.00489.x
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size Reduction Effectively Enhances the Intestinal Health‐Promotion Ability of an Orange Insoluble Fiber in Hamsters

Abstract: The effects of particle size changes by micronization on the intestinal health-promotion ability of orange insoluble fiber fraction (IFF) were investigated in a hamster model by feeding 3 diets, which contained unmicronized IFF (control), jet-milled IFF, and high-pressure micronized IFF as the sole fiber source in diet. The results showed that the micronization treatments significantly altered the physicochemical properties of insoluble fiber. The consumption of the micronized fibers (6.26 to 11.4 microm) at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…2004; Chau et al . 2007), sweet orange (Wu et al . 2007), sweet potato and white potato (Mullin and Wolynetz 1995), red wheat bran, peanut hull and corn pericarp (Heller et al .…”
Section: Resultsmentioning
confidence: 99%
“…2004; Chau et al . 2007), sweet orange (Wu et al . 2007), sweet potato and white potato (Mullin and Wolynetz 1995), red wheat bran, peanut hull and corn pericarp (Heller et al .…”
Section: Resultsmentioning
confidence: 99%
“…The application of micro-fractionation in food research revealed that the reduction of the particle size of various fiber-rich plant materials modifies the structure, surface area and functional properties of the particles. Chau et al (2007) and Wu et al (2007) hypothesized that subjecting plant insoluble fibre to different treatments like ball milling, jet milling, high-pressure micronization resulted in the rearrangement of fibres from insoluble to a soluble form, which improved their physicochemical properties and put forth a favourable effect on improving intestinal function and general health as seen in in vivo studies.…”
Section: Fractionationmentioning
confidence: 99%
“…doi:10.1016/j.foodres.2010.01.005 recently gained importance in connection with the development of new functional materials in various industrial application including the foodstuff sector (Choi, Chung, Yoon, & Kim, 2001); but unfortunately, so far the use of this technology in DF processing remains rather limited, probably due to the toughness and polymer nature of DF and inadequate equipment support. Most of previous works use milling under high speed shear stress to pulverize this kind of material; yet to date only two studies are found using high-pressure micronization treatment in manufacturing insoluble DF of orange and carrot origin, which effectively pulverize the DF particles to 6.26 lm and 7.23 lm, respectively (Chau, Wang, & Wen, 2007;Wu, Chien, Lee, & Chau, 2007). Further studies attempting to produce DF powders on submicron scale are badly needed, and information of the effects of micro/nanotechnology on the particle sizes, characteristics and physicochemical properties of DF could give useful insight into its potential applications in the food industry.…”
Section: Introductionmentioning
confidence: 99%